Confidence Estimation and Boosting for Dynamic-Comparator Transient-Noise Analysis - Conrad, Joschua; Kauffman, John; Wilhelmstatter, Simon; Asthana, Rohan; Belagiannis, Vasileios; Ortmanns, Maurits (2024 22nd IEEE Interregional NEWCAS Conference (NEWCAS), 2024)
While designing a comparator, simulation of input-referred noise is crucial. While periodic steady state analyses allow a fast simulation, they are cumbersome to set-up, not compatible with all kinds of circuit models, and require to know the noise-critical operating time within a period. On the contrary, the comparator can be analyzed in a noisy transient simulation with a small test-voltage applied. The noise and offset characteristics can then be derived from a number of simulated comparator decisions and a statistical model. This method is easy to set-up, but has two fundamental simulation parameters: the number of simulated comparator decisions and the magnitude of the applied test-voltage. In this work we derive the statistical confidence into the estimated input-referred noise and show how it depends on the two simulation parameters. It is then shown that this confidence also depends on the true (unknown) input-referred noise. To solve that issue, an algorithm for boosting the convergence is introduced. This algorithm iteratively simulates the comparator decisions and updates the test-voltage for granting a known confidence into the estimated input-referred noise. The algorithm implemented in Verilog-A is available under https://github.com/Joschua-Conrad/Transient-Simulation-of-Dynamic-Comparator-Noise.
CRIS-Team Scopus Importer:2025-02-04
Keywords: Confidence; Dynamic Comparator; Simulation; Transient Noise Analysis